Phenotypic And Genotypic Characteristics Of Foodborne Bacteria Associated With Biofilm Formation In Fresh Ulam - Anis Athirah Binti Bahri (Universiti Malaysia Terengganu, 2022)
Ulam are important food among the Malays because of their nutritional values, and their consumption is increasing. However, the foodborne outbreak which is associated with eating raw ulam may pose health risks to the consumers by increasing crosscontamination, antibiotic-resistant bacteria and biofilm formation. The objectives of